2010
DOI: 10.1590/s0104-11692010000300005
|View full text |Cite
|
Sign up to set email alerts
|

The attitudes of nurses from an intensive care unit in the face of errors: an approach in light of bioethics

Abstract: This study analyzed the attitudes of nurses concerning the occurrence of errors in nursing procedures carried out in an Intensive Care Unit (ICU) based on the bioethics framework.This descriptive study with qualitative approach was carried out with 14 nurses from a private hospital in the city of São Paulo, Brazil. Results were analyzed according to Bardin's proposal of content analysis. The resulting themes were: acknowledging one's fallibility; acknowledging and reporting errors; hiding errors. The nurses' r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 5 publications
0
20
0
2
Order By: Relevance
“…The patients and their families have the right to know the truth and this information is essential to maintain their confidence in the work of the team. (15) However, a study on medication errors in hospitalized children in a pediatric intensive care unit for treatment of cancer patients identified that 95.5% of the patients victims of errors and their families were not notified of its occurrence by the health team. (16) The fact that 100 students (91.6%) agree that there is a great difference between what professionals know, what is right and what is seen in daily healthcare explains the fact that the consistent interconnection between theory and practice is not something experienced in Brazilian health institutions.…”
Section: Discussionmentioning
confidence: 99%
“…The patients and their families have the right to know the truth and this information is essential to maintain their confidence in the work of the team. (15) However, a study on medication errors in hospitalized children in a pediatric intensive care unit for treatment of cancer patients identified that 95.5% of the patients victims of errors and their families were not notified of its occurrence by the health team. (16) The fact that 100 students (91.6%) agree that there is a great difference between what professionals know, what is right and what is seen in daily healthcare explains the fact that the consistent interconnection between theory and practice is not something experienced in Brazilian health institutions.…”
Section: Discussionmentioning
confidence: 99%
“…Almost all studies adopt the point of view of nursing professionals (Telles Filho, Praxedes, 2009). Also, few Brazilian studies have addressed either the ethical aspects involved in medication errors or the most adequate way to address these situations (Coli et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…However, the fact errors are going unreported confirms that a punitive culture is still in effect (24) .…”
Section: Discussionmentioning
confidence: 99%